HYDRO ECOLOGICAL MONITORING OF AQUATIC ECOSYSTEMS TAKING INTO ACCOUNT THE CURRENT EUROPEAN TRENDS IN ENVIRONMENTAL ACTIVITIES - Клименко, М. О.; Клименко, О. М.; Петрук, А. М. (Scientific Progress & Innovations, 2013)
The authors analyzed hydro ecological monitoring of aquatic ecosystems (cooling pond Khmelnitskyi and White Lake) taking into account the current European trends in environmental activities. Hydro ecological monitoring of aquatic ecosystems (cooling pond Khmelnitskyi and White Lake) taking into account the current European trends in environmental activities. The strategy of taking management decisions to improve the ecological status of aquatic ecosystems is offered. The system of monitoring observations and complex integrated assessments of water reservoir located in the zone of nuclear energy in accordance with the regulatory framework of the EU on the basis of a systematic approach and a comprehensive analysis of the environmental condition of the water reservoir is improved.